Mercaptoacetamide: A promising zinc-binding group for the discovery of selective histone deacetylase 6 inhibitors - Tavares, Maurício T. (Eur J Med Chem, 2020)
Histone deacetylase 6 (HDAC6) is a zinc-dependent HDAC that mainly modulates the acetylation status of non-histone substrates, such as α-tubulin and heat shock protein 90 (HSP90). The activity of HDAC6 plays a critical role in cell proliferation, protein trafficking and degradation, cell shape, migration, as well as regulation of immunomodulatory factors. For this reason, HDAC6 influences the progress of cancers, neurodegenerative disorders, and autoimmune responses. In the last few years, the discovery of selective HDAC6 inhibitors (HDAC6is) has become an attractive research area as five HDAC6is are being investigated in phase I/II clinical trials. However, the hydroxamic acid functional group still represents the predominant zinc-binding group (ZBG), that often suffers from poor pharmacokinetics and mutagenic potential, thus impairing the application of hydroxamate-based HDAC6is for long-term therapies. On the other hand, mercaptoacetamide (MCA)-based HDAC6is comprise a class of compounds that, in some cases, display nanomolar HDAC6 potency and a thousand-fold selectivity over class I HDAC isozymes. Moreover, MCA-based HDAC6is lack the mutagenicity associated with the hydroxamate function and display pharmacological effects, demonstrating the potential of this particular ZBG to improve upon the drug-like properties of HDAC6is. Herein, we summarize for the first time the structure-activity relationships (SARs) of MCA-based HDAC6is, discuss their HDAC6 selectivity at the molecular level using inhibitor-HDAC co-crystal structures, and further provide our perspective regarding their drug metabolism, pharmacokinetics, and pharmacological properties.